A study of heating rate effect on the photocatalytic performances of ZnO powders prepared by sol-gel route: Their kinetic and thermodynamic studies - TÜNÇAY, MEHMET MASUM; DEMİRCİ, SELİM (ELSEVIER, 2020)
In this work, ZnO particles were fabricated by sol-gel method at different heating rate at 500 degrees C for 2 h. The ZnO powders were analysed by X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), UV-vis spectroscopy and photoluminescence, respectively. The effect of heating rate on photocatalytic activities of ZnO particles was evaluated by degradation of methylene blue (MB). The non-isothermal kinetics and thermodynamic properties were also estimated. The XRD results showed that ZnO had hexagonal wurtzite structure. The different heating rate didn't influence the surface morphology of ZnO powders. It was observed that the heating rate had a profound effect on reduction of band gap and photocatalytic performances. The band gap of the ZnO particles varied from 3.10 to 3.17. The ZnO sample prepared at 1 degrees C/min exhibited the highest photocatalytic activity. Its relative photocatalytic degradation rate and kinetic constant were 92.7% and 1.069x10(-2) min(-1), respectively. The results might be ascribed to low bulk vacancies, high surface oxygen vacancies and narrow band gap energy. Also, ZnO photocatalysts showed good stability after four sequence tests. This study provides a new strategy to improve the photocatalytic performances of ZnO photocatalyst for the degradation of organic contaminant.
Keywords: Sol-gel method; Heating rate; Particle; Thermodynamic properties; Photocatalytic activity; ZINC-OXIDE NANOPARTICLES; METHYLENE-BLUE; THIN-FILMS; OPTICAL-PROPERTIES; CARBON NANOTUBES; AQUEOUS-SOLUTION; GREEN SYNTHESIS; DEGRADATION; PHOTOLUMINESCENCE; TEMPERATURE